O ORGANIZAR DO SINDICATO: PRÁTICAS COTIDIANAS NO FAZER SINDICAL - Mongin, Saulo Bayerl (2020)
The present dissertation aims to understand the constitution of Adufes, a union entity of Brazilian university teaching unionism, as a space for participation, based on organizational practices engendered by its members, in the everyday organizational pra